Doing Things Differently: Transformation, Innovation and Student Success in CTA and ITC - Kraus, Tracy Louise (College of Accounting, 2022)
The need for racial transformation within the accounting profession has been highlighted in recent years and consequently, efforts have been made by numerous players to further support accounting students pursuing the chartered accountant designation. This research focuses on an innovative postgraduate accounting programme, referred to as a Certificate in Theory of Accounting (CTA), offered by a private higher education institution, CA Connect. The research examines the factors associated with academic success in that programme as well as the subsequent initial professional board exam, known as the Initial Test of Competence (ITC). The variables considered are students' demographic details (age, gender and race), prior academic performance, prior tertiary institution, previous CTA attempts, time lapses between undergraduate and postgraduate study and class format selection. While this research repeats prior work done in public education contexts within the private higher education space, it is also novel, in that it extends prior research by examining several variables which have not been investigated before, neither in the South African context nor abroad. Three logistic regression models were developed, employing both forced entry and hierarchical regression methods. The findings confirm prior research which suggests that previous academic performance is strongly positively associated with future academic success and that race is a key determinant of success, most notably in CTA. Prior tertiary institution and attending fulltime, contact classes were also found to be associated with success at CTA level. However, adopting an after-hours, blended learning approach to CTA was found to be associated with success in the ITC. These findings provide further evidence of the need for continued grassroots interventions to allow scholars and students to build upon the strongest possible educational foundation and show a link between the innovations introduced by CA Connect and student success in the ITC.